The enlightenment of bladder cancer treatment: origin and progress of photodynamic diagnosis. (September 2011) - Otto, Wolfgang; Burger, Maximilian; Fritsche, Hans-Martin; Rößler, Wolfgang; Wieland, Wolf F; Denzinger, Stefan
Compared with prostate cancer, which exclusively affects male patients, urothelial bladder cancer is the most common urogenital carcinoma affecting both men and women. In approximately 75% of cases, bladder cancer occurs as multifocal nonmuscle-invasive papillary tumor that demonstrates high rates of recurrence, leading to frequent transurethral resections with the need of hospitalization. These cases have paved the way for photodynamic diagnosis. Since the 1990s, this technique has been used to identify bladder tumors, especially highly aggressive carcinoma in situ, in an easier and more complete way compared with conventional white-light cystoscopy. This article gives an up-to-date review of the method, indication and results of photodynamic diagnosis for treatment of urothelial bladder cancer.